Epiphytic lichens as indicators of environmental quality around a municipal solid waste landfill (C Italy). (August 2015) - Paoli, Luca; Grassi, Alice; Vannini, Andrea; Maslaňáková, Ivana; Bil'ová, Ivana; Bačkor, Martin; Corsini, Adelmo; Loppi, Stefano
Highlights: We investigated the effects of air pollution around a MSW landfill using lichens. Lichen diversity increased and heavy metal depositions decreased with distance. We detected physiological alterations in the lichens close to the landfill. Lichens are suitable bioindicators of environmental quality around MSW landfills. Abstract: Epiphytic lichens have been used as indicators of environmental quality around a municipal solid waste landfill in C Italy. An integrated approach, using the diversity of epiphytic lichens, as well as element bioaccumulation and physiological parameters in the lichen Flavoparmelia caperata (L.) Hale was applied along a transect from the facility. The results highlighted the biological effects of air pollution around the landfill. The Index of Lichen Diversity (ILD) increased and the content of heavy metals (Cr, Cd, Cu, Fe, Ni and Zn) decreased with distance from the landfill. Clear stress signals were observed in lichens growing in front of the facility, i.e. discoloration, necrosis, membrane lipid peroxidation, lower ergosterol content, higher dehydrogenase activity. Decreased photosynthetic efficiency, altered chlorophyll integrity and production of secondary metabolites were also found. The results suggested that lichens can be profitably used as bioindicators of environmental quality around landfills.